High night temperature during maize post-flowering increases night respiration and reduces photosynthesis, growth and kernel number - Kettler, Belén Araceli; Carrera, Constanza Soledad; Nalli Sonzogni, Federico David; Trachsel, Samuel; Andrade, Fernando Hector; Neiff, Nicolás (Wiley, 2022)
In the last years globally, daily night-time low temperatures have increased more than twice compared with maximum temperatures. There is little evidence about maize growth and yield responses to high night temperature (HNT) under field conditions. In this study, we aimed to (i) evaluate the effect of HNT during post-flowering on kernel number (KN), crop growth rate expressed in chronological days and thermal units (CGRD and CGRTU, respectively), radiation use efficiency (RUE), night respiration (Rn), net photosynthesis (Amax), chlorophyll fluorescence and cell membrane stability (CMS), and (ii) identify associations among the measured physiological traits. Two hybrids (Te, temperate; and St, subtropical) were exposed to two thermal conditions from R1 + 2d to R1 + 16d: (i) HNT from 1900 to 0700 h, and (ii) ambient night temperature (ANT). The HNT resulted in reductions in KN (8%), CGRD (11%), and CGRTU (19%), with non-significant changes in kernel weight and grain yield. Reductions in KN were better explained by drops in CGRTU than in CGRD. Under HNT, Amax significantly decreased (p < 0.05; 17%, among experiments and hybrids) with insignificant changes in CMS and chlorophyll fluorescence. HNT caused a larger effect on Rn in Te (+40%) than in St. We found a strong negative relationship between Rn and Amax, indicating that high Rn might exhibit an indirect effect on Amax, altering carbon balance and growth.